Are Sitting Position and Working Duration Associated with Low Back Pain in Workers?: A Meta-Analysis - Prianggi, Herawati; Murti, Bhisma; Prasetya, Hanung (Journal of Epidemiology and Public Health, 2021)
Background: Low back pain (LBP) is general